Google Guice Agile Lightweight Dependency Injection Framework - Vanbrabant, Robbie. (Apress : Imprint: Apress, 2008)
Guice (pronounced “Juice”) is the Jolt Award-winning, 100% Java icing on the cake of Java dependency injection. Unlike other popular dependency injection frameworks such as Spring, Guice fully embraces modern Java language features and combines simplicity with stunning performance and developer–friendliness. Google Guice: Agile Lightweight Dependency Injection Framework will not only tell you “how,” it will also tell you “why” and “why not,” so that all the knowledge you gain will be as widely applicable as possible. Filled with examples and background information, this book is an invaluable addition to your knowledge of modern agile Java. Learn simple annotation–driven dependency injection, scoping and aspect-oriented programming, and why it all works the way it works Be the first to familiarize yourself with concepts that are likely to be included in a future Java EE or SE release (through JSR 299) Get things done without having to write any XML.